176 The anticontractile actions of adrenergic and non-adrenergic agonists on perivascular adipose tissue are mediated via distinct signalling pathways. (6th June 2015) - Bussey, Charlotte; Withers, Sarah; Bodagh, Neil; Edwards, Gillian; Heagerty, Anthony
Abstract : Objective: Healthy perivascular adipose tissue (PVAT) exerts an anticontractile effect in response to various vasoconstrictor agonists which is lost in diabetes and hypertension. Solution transfer experiments have demonstrated the existence of an adipocyte-derived relaxing factor (s) that mediates anticontractile function; however controversy exists surrounding the release mechanisms and its identity. This study aimed to elucidate the pathways involved in the anticontractile response to adrenergic and non-adrenergic agonists. Methods: The effects of PVAT on the contractility of isolated rat mesenteric arteries were investigated using wire myography. Concentration-response curves were generated to noradrenaline, phenylephrine or serotonin (1 × 10 –5 –3 × 10 –9 mol.l –1 ) following 30 min incubation with the ß3-agonist, CL-316, 243 (10 µmol.l –1 ); ß3-antagonist, SR59230A (30 µmol.l –1 ); NOS inhibitor, L-NMMA (100 µmol.l –1 ); BKCa channel inhibitor, iberiotoxin (100nmol.l -1 ) or the KCNQ inhibitor, XE 991 (10 µmol.l –1 ). Results and conclusions: PVAT elicited an anticontractile effect in response to both noradrenaline and serotonin, but not phenylephrine (noradrenaline: P<0.01, serotonin: P<0.05, phenylephrine: P=0.8321). In vessels with PVAT, CL-316, 243 abrogated the vasoconstrictor effect of phenylephrine (P<0.01), but not noradrenaline (P=0.9057). Moreover, incubation with SR59230A potentiated the response to noradrenaline in vessels with PVAT (P<0.05) suggesting a role for 3-adrenergic signalling in mediating noradrenaline-induced PVAT function. The presence of L-NMMA produced an increase in the vasoconstrictor action of noradrenaline in vessels with PVAT (P<0.05) indicating that nitric oxide plays a role in the adrenergic-dependent PVAT anticontractile effect. This was reaffirmed by observations of 3-adrenoceptor and eNOS expression within PVAT using western blotting. ß3-adrenoceptor manipulation did not alter the serotonin-induced PVAT anticontractile effect (SR 59230A: Incubation with iberiotoxin abrogated PVAT function in response to noradrenaline (P < 0.001) and serotonin (P < 0.001) suggesting involvement of BKCa channel activation in both signalling pathways. However, the presence of XE 991 reversed the noradrenaline-induced PVAT anticontractile effect (P < 0.001) but had no effect on the serotonin-induced effect (P = 0.9417) indicating a role for KCNQ channel activation in the 3-dependent anticontractile effect. Overall, this study indicates that PVAT exerts an agonist-dependent anticontractile effect via distinct mechanisms potentially leading release of a number of adipocyte-derived relaxing factors.